2005
DOI: 10.1007/s00442-005-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic fungus promotes plant invasion into diverse communities

Abstract: Reducing the biological diversity of a community may decrease its resistance to invasion by exotic species. Manipulative experiments typically support this hypothesis but have focused mainly on one trophic level (i.e., primary producers). To date, we know little about how positive interactions among species may influence the relationship between diversity and invasibility, which suggests a need for research that addresses the question: under what conditions does diversity affect resistance to invasion? We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 66 publications
(72 reference statements)
6
69
1
Order By: Relevance
“…In a microcosm study, Omacini et al (2009) observed that endophyte infection increased L. multiXorum recruitment across a range of microsite conditions created by litter deposition and soil water availability. Laboratory studies also showed enhanced establishment of Lolium arundinaceum (tall fescue) when infected by fungal endophytes (Clay 1987;Rudgers et al 2005). Yet comparable evidence from Weld studies has been extremely rare (Eerens et al 1998).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a microcosm study, Omacini et al (2009) observed that endophyte infection increased L. multiXorum recruitment across a range of microsite conditions created by litter deposition and soil water availability. Laboratory studies also showed enhanced establishment of Lolium arundinaceum (tall fescue) when infected by fungal endophytes (Clay 1987;Rudgers et al 2005). Yet comparable evidence from Weld studies has been extremely rare (Eerens et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Parker and Gilbert 2007;Borer et al 2007;Mangla et al 2008). In contrast, although mutualistic plant-microbe interactions have recently become a focus of invasion research (Richardson et al 2000;Klironomos 2002;Callaway et al 2004;Rudgers et al 2005;Stinson et al 2006;Nuñez et al 2009), their role in a variety of systems has yet to be established (Desprez-Loustau et al 2007).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, associations of grass plants with fungal endophytes belonging to the Clavicipitaceae family and residing in aboveground plant parts, have become the subject of detailed ecological studies (Clay et al, 2005;Rudgers et al, 2005;Finkes et al, 2006;Meister et al, 2006). These fungi occur in 20% to 30% of all grass species (Leuchtmann, 1993) with their hyphae growing in the apoplastic space without penetrating into plant cells and generally causing no visible symptoms of infection (Christensen et al, 2008).…”
mentioning
confidence: 99%
“…They provide protection to their hosts against insect pests 27) , herbivores 11) , and microbial pathogens 39,42,44) . Fungi present in healthy tissues of plants can promote the invasion of host plant communities with greater species diversity 37) and alter the nutrient cycle in individual plants 18) and in ecosystems 24) . The isolation and characterization of fungal communities will help us to estimate the diversity of fungi 2) , since the true scale of fungi is open to debate 21,26) .…”
mentioning
confidence: 99%